2014
DOI: 10.1159/000360516
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Treatment of Primary Biliary Cirrhosis

Abstract: The natural history of primary biliary cirrhosis (PBC) has improved greatly during the past two decades because of its diagnosis at earlier stages and the widespread use of ursodeoxycholic acid as first-line treatment. As a result, far fewer patients require liver transplantation and patients diagnosed with early-stage disease appear to have a normal life expectancy. The evidence-based treatment of PBC is reviewed here. The challenge of designing and executing high-quality clinical trials as well as lessons fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Administration of ursodeoxycholic acid (UDCA) is the standard of care for PBC patients [35] and is recommended by major guidelines. [6,7] The primary therapeutic action of hydrophilic UDCA is to replace hydrophobic bile acids, thereby attenuating cholestasis and hepatocellular injury.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of ursodeoxycholic acid (UDCA) is the standard of care for PBC patients [35] and is recommended by major guidelines. [6,7] The primary therapeutic action of hydrophilic UDCA is to replace hydrophobic bile acids, thereby attenuating cholestasis and hepatocellular injury.…”
Section: Introductionmentioning
confidence: 99%
“…14 Studies have shown significant improvement of ALP and changes in liver histology in PBC patients treated with budesonide. [24][25][26][27] Hirschfield et al 27 found that in PBC patients with a poor response to UDCA, the combination of UDCA and budesonide for 36 months did not improve the histological progression, but the proportion of patients with normal ALP (35%) was significantly higher than that in the placebo group (9%, p=0.023). The clinical trials are not large enough, so larger trials and more complete clinical trial evidence are needed to confirm the benefits of budesonide in the treatment of PBC.…”
Section: Treatment Of Pbcmentioning
confidence: 99%
“…We have known for about 40 years that UDCA has a “hepatoprotective” effect. There is good evidence for the beneficial effect of UDCA in PBC ( Poupon, 2014 ). Yet, the proof of a beneficial influence for other chronic liver diseases such as PSC or metabolic liver diseases is much lower or nonexisting ( Reardon et al, 2016 ; de Vries and Beuers, 2017 ).…”
Section: Possible Interventionsmentioning
confidence: 99%